Hearts Set to Obey - Meilaender, Gilbert (Dialog, 2004)
Caught in the tension between the reality of our sin and the reality of God's forgiveness and grace, how are we to obey the commandments of God and strive for a holy life? Many have argued that the Lutheran tradition has undermined the ethical imperative of the Christian walk. While it is true that Lutheran theology in some modes has denied the sort of linear moral progress emphasized by some other traditions, it affirms the reality of genuine transformation in the Christian life, which moves us beyond the static Sisyphean tension in which we are simultaneously sinners and saints. Though emphasizing grace as pardon and righteousness as relational, Lutheran theology also has place for a grace that empowers believers for growth in discipleship. The terms ‘justification’ and ‘sanctification’ point not to different works of God but to two different angles—pardon and power—from which to describe the one work of God in Christ, reconciling the world to himself. In light of this, we need not sever ethics from theology to understand how our hearts may be set to obey the commandments of God.